2008
DOI: 10.1002/hyp.7038
|View full text |Cite
|
Sign up to set email alerts
|

Lateral flow thresholds for aspen forested hillslopes on the Western Boreal Plain, Alberta, Canada

Abstract: Abstract:To predict the long-term sustainability of water resources on the Boreal Plain region of northern Alberta, it is critical to understand when hillslopes generate runoff and connect with surface waters. The sub-humid climate (P Ä ET) and deep glacial sediments of this region result in large available soil storage capacity relative to moisture surpluses or deficits, leading to threshold-dependent rainfall-runoff relationships. Rainfall simulation experiments were conducted using large magnitude and high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 30 publications
3
85
0
1
Order By: Relevance
“…The peatland-pond complexes are located on a topographical high glacial till moraine adjacent to an upland forested hill slope reaching a height of 7 m above the pond surface. The pond and peatlands are located in a recharge zone, and water tables typically grade away from the peatland into the adjacent hillslope (Ferone and Devito, 2004;Redding and Devito, 2008). There is some disturbance associated with access roads for oil drilling located outside the study peatland-pond complex, and seismic lines (where strips of vegetation are removed) occur through upland and peatland landscape units.…”
Section: Site Descriptionmentioning
confidence: 98%
“…The peatland-pond complexes are located on a topographical high glacial till moraine adjacent to an upland forested hill slope reaching a height of 7 m above the pond surface. The pond and peatlands are located in a recharge zone, and water tables typically grade away from the peatland into the adjacent hillslope (Ferone and Devito, 2004;Redding and Devito, 2008). There is some disturbance associated with access roads for oil drilling located outside the study peatland-pond complex, and seismic lines (where strips of vegetation are removed) occur through upland and peatland landscape units.…”
Section: Site Descriptionmentioning
confidence: 98%
“…High variability during wet periods was attributed to the combination of well-drained soils and steeply sloping terrain in Pennsylvania (Takagi and Lin, 2011). Moreover, studies have shown that hydrologic flowpaths change over time from vertical infiltration during wet-up to subsurface lateral flow at or near saturation causing redistribution of moisture across the landscape (Redding and Devito, 2008;Rains et al, 2006;Swarowsky et al, 2012).…”
Section: Temporal Stability Of Terrain-shape Indicesmentioning
confidence: 99%
“…Soil temperature and heat storage in the upper 0.05 m were measured using a thermocouple probe (TCAV-L; Campbell Scientific Inc.) inserted at 0.025 and 0.075 m below the soil surface. Soil volumetric moisture content (VMC, %) (CS616 TDR; Campbell Scientific Inc.; calibrated for study-site soils) and soil temperatures (107B thermistors; Campbell Scientific Inc.) were recorded at depths of 0.01, 0.10, 0.30, 0.50, and 1.0 m below the litter fall horizon -mineral soil interface at each site (Redding and Devito 2008;Brown et al 2013). VMC data were corrected for soil bulk density and temperature.…”
Section: Meteorological Data Collectionmentioning
confidence: 99%